1986
DOI: 10.1002/aic.690320308
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radial velocities on laminar flow, tubular reactor models

Abstract: Existing models for laminar flow in tubular reactors neglect radial velocities in the momentum transport equation. The axial velocity distribution is calculated assuming fully developed flow wherein axial velocities are in local equilibrium with the radial viscosity profile. A test of this assumption has been devised using a representative model of the Newtonian viscosity, μ(r, z), and by reconstructing the radial velocity components using the continuity equation. The assumption of fully developed flow is show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

1987
1987
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 4 publications
0
3
0
3
Order By: Relevance
“…balanços das concentrações de monômero (C M -mol/l), iniciador (C I -mol/l) e solvente (C S -mol/l), além dos balanços para os momentos do polímero morto de ordem zero (µ 0 ), um (µ 1 ) e dois (µ 2 ) [5,14,19,20] : . As equações obtidas para os momentos do polímero vivo de ordem zero (λ 0 ), um (λ 1 ) e dois (λ 2 ) são apresentadas a seguir, respectivamente [20] :…”
Section: Parâmetrounclassified
See 2 more Smart Citations
“…balanços das concentrações de monômero (C M -mol/l), iniciador (C I -mol/l) e solvente (C S -mol/l), além dos balanços para os momentos do polímero morto de ordem zero (µ 0 ), um (µ 1 ) e dois (µ 2 ) [5,14,19,20] : . As equações obtidas para os momentos do polímero vivo de ordem zero (λ 0 ), um (λ 1 ) e dois (λ 2 ) são apresentadas a seguir, respectivamente [20] :…”
Section: Parâmetrounclassified
“…Realizando um balanço de energia em um volume de controle do reator tubular e desenvolvendo os operadores matemáticos para um sistema em coordenadas cilíndricas, obteve-se a seguinte equação diferencial parcial para estimar a temperatura (T em Kelvin) ao longo do reator tubular [5,14,19,20] .…”
Section: Parâmetrounclassified
See 1 more Smart Citation
“…We use what has become the standard transport model for a tubular polymerization reactor in laminar flow. ,, Axial diffusion and conduction are ignored. Thermal conductivity, heat capacity, and the heat of polymerization are treated as constants.…”
Section: Process Model For a Tubular Reactormentioning
confidence: 99%
“…In 1983, a convective diffusion non‐Newtonian tubular flow under developing flow conditions was investigated by Venkatsubramanian and Mashelkar 12. A year later, McLaughlin et al13 studied the effect of radial velocity in a tubular laminar flow reactor. They showed that the radial velocity should not be neglected when the convective diffusion of heat and mass is considered.…”
Section: Introductionmentioning
confidence: 99%